Comparison of Xenogeneic Collagen Matrix vs. Free Gingival Grafts to Increase the Zone of Keratinized Mucosa Around Functioning Implants. Issue 1 (February 2019) - Vellis, Jimmy; Kutkut, Ahmad; Al-Sabbagh, Mohanad
Abstract : Purpose: To evaluate the effectiveness of collagen matrix (CM) grafts as an alternative to free gingival grafts (FGGs) in increasing the zone of keratinized tissue (KT) around dental implants. Methods: Thirty subjects with 2 contralateral implants were recruited. The test group (n = 30) received CM grafts. The control group (n = 30) received FGGs. Clinical variables were plaque index, gingival index, probing depths, bleeding on probing (BOP), and mucosal recession (MR). Subjects were followed at 1 and 2 weeks and 1, 3, and 6 months. Results: FGGs resulted in mean gains (3.73 ± 1.93 mm) in KT for 28 of 30 implants (93% success rate). CM grafts resulted in mean gains (3.23 ± 1.52 mm) in KT for 29 of the 30 implants (97% success rate). Mean change in pocket depth around implants grafted with FGG was −0.24 ± 1.02 mm and with CM was −0.25 ± 0.80 mm. Mean change in BOP around implants grafted with FGG was 0.03 ± 0.49 and with CM was 0.13 ± 0.57. Conclusion: CM grafts achieved results comparable to those of FGGs in augmented tissue. They do not negatively affect probing depths, MR, or bleeding on probing.